People and Fresh Water Ecosystems: Pressures, Responses and Resilience - Matthews, Nathaniel (Elsevier, 2016)
Freshwater ecosystems are central to the global water cycle, in local generation of freshwater flows, and the healthy functioning and resilience of other ecosystems. Freshwater security depends on healthy ecosystems. Current human threats to freshwater ecosystems include rapid infrastructure development and land-use change, inefficient water use and over-abstraction, and pollutants. These threats, combined with increasing demand for water resources, exacerbate the sustainable development challenge. By 2025, two-thirds of the world's population may be living in conditions of severe water stress. It is essential to find solutions that provide for the maintenance of freshwater ecosystems while meeting human needs. This paper examines responses to three pressures to freshwater ecosystems: declining ecosystem services, hydropower and urban development. It explores opportunities for improved decision-making and enhanced resilience including: better evaluation of trade-offs and interlinkages; improved monitoring; decision-making that incorporates long-term perspectives and risks; and the leveraging of crises to advance change.